Market Innovation and Competitive Advantage in Telecommunication Companies in Kenya - Peter C Mugo; Jimmy Macharia (European Journal of Management Issues, 2021)
Purpose: To survive, organizations must have a competitive advantage in order to stay ahead of the competition. Market innovation has remained the driving force behind most market expansions and stability in the turbulent nature of global economies. This study sought to establish the influence of market innovation on the competitive advantage of telecommunication companies in Kenya.